The Effectiveness Of Health Education Interventions On Stress, Anxiety, And Depression Among Pregnant Women : A Systematic Review - Wulandari Wulandari; Hanik Endang Nihayati; Ni Ketut Alit Armini (Universitas Pahlawan Tuanku Tambusai, 2025)
Pregnancy is a vulnerable phase often accompanied by stress, anxiety, and depression, which may negatively impact both maternal and fetal health. One approach to managing psychosocial problems during pregnancy is through health education delivered directly to pregnant women. This study aims to Investigate role of direct health education interventions in decreasing stress, anxiety, and depression throughout pregnancy. The method A systematic review was conducted following the PRISMA guidelines by searching the Scopus, PubMed, and ProQuest databases. Study quality was systematically appraised utilizing the Joanna Briggs Institute (JBI) Critical Appraisal Tool. This review analyzed 12 randomized controlled trials (RCTs) conducted across six countries. Results: Of the 892 articles identified, 12 met the inclusion criteria, involving 30–1324 pregnant women across six countries. Health education interventions, including mindfulness, antenatal psychoeducation, cognitive-behavioral stress management (CBSM), lifestyle education, and spiritual approaches, were shown to reduce stress, anxiety, and depression, while enhancing self-efficacy, emotional regulation, childbirth preparedness, Maternal infant attachment, and healthy behaviors. The conclusion of this systematic review found that effective health education can improve the mental health of pregnant women and needs to be implemented as a promotive-preventive strategy during pregnancy. Keywords: Education, Stress, Anxiety, Depression, Pregnant Women